PENGARUH ORIENTASI PEMBELAJARAN, KEMAMPUAN DAN ORIENTASI PASAR TERHADAP STRATEGI BISNIS DAN KINERJA KEUANGAN - J.E. Sutanto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
One indicator of company’s or business’s successfulness in the competition was the company or business must have competitive advantage that allowed the industrial company of foods and beverages yielding the superiority of production result than their competitors in the determining the strategy and financial performance continually. The population of this research was foods and beverages industry especially big and medium industrial company, which have multi-business and multi-products   in the East Java area that consist of 1286 industrial companies of foods and beverages according to the Indonesian Business Field Classification  (KLUI 15) years 2002. The data analysis technique used Structural Equation Modeling = SEM) with computer help used AMOS program 4.0 version. The research result indicated that: (1) teaching orientation has positive influence and significant toward the financial performance, (2) production capability has positive influence and significant toward the financial performance, (3) market orientation has positive influence and significant toward the financial performance , (4) teaching orientation has positive influence and significant toward the business strategy, (5) production capability has positive influence and significant toward the business strategy, (6) market orientation has positive influence and significant toward the business strategy, (7) simultaneously the influence of teaching orientation, production capability and market orientation toward business strategy and financial performance was proper as the created model